2020
DOI: 10.24200/sci.2020.54534.3797
|View full text |Cite
|
Sign up to set email alerts
|

Modified Cache-Template Attack on AES

Abstract: CPU caches are a powerful source of information leakage. To develop practical cache-based attacks, there is an increasingly need to automate the process of finding exploitable cache-based side-channels in computer systems. Cache template attack is a generic technique that utilizes Flush+Reload attack in order to automatically exploit cache vulnerability of Intel platforms. Cache template attack on T-table-based AES implementation consists of two phases including the profiling phase and the key exploitation pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study demonstrated a Cache template attack on T-table against AES [36]. The cache's behaviour disclosed the input in its entirety or part.…”
Section: Advanced Encryption Standardmentioning
confidence: 99%
“…A study demonstrated a Cache template attack on T-table against AES [36]. The cache's behaviour disclosed the input in its entirety or part.…”
Section: Advanced Encryption Standardmentioning
confidence: 99%